Significance of Pelleting The Seed with Phosphate and Lime on The Cultivation of Soybean in Acid Soils in Sitiung, West Sumatera - Setiyo Hadi Waluyo (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2005)
Several experiments containing 2 field, 2 pot and I rhizotron were conducted to develop a low input agricultural practice(pelleting seed) for production of soybean plant (cv. Tidar) on heavily acid soils of Sitiung, West Sumatra. The field and polexperiments were conducted in Sitiung and in the greenhouse at the Agriculture Division, Center for the Application ofIsotopes and Radiation Technology, National Nuclear Energy Agency, Jakarta, respectively, in 1990 - 1992. The rhizotronexperiment was conducted in 1994 at the Laboratory of Microbiology, Department of Agrotechnology and Food Sciences.Wageningen University. Wageningen, The Netherlands. Lime-pel/eting seeds with the equivalent of 50 kg lime ha·1 increased nodulation, growth and yield both in unlimed and limed soils. Considerable increases in nodulatio, growth and yield were obtained when a small amount of P fertiliser (J 0 kg TSP ha·l ) was incorporated in the lime-pellet. The beneficial effects of both lime-pelleting and [lime+TSPj-pelleting were more pronounced on nodulation than on growth and yield. and greater in umimed soils than in limed soils. Large effects were obtained in nodulation, growth and yield of soybean in field experi1ltl!nts by pelleting seeds with lime or with lime + TSP. However, the pel/eted soybean plants grown in unlimed soils remained small and yields were negligible. To sustain growth and production of soybean in these acid soils, adequate quantities of lime and of P fertiliser would be necessary. In the present study, a combination of broadcast lime at 2.0 t ha-I with [lime+TSPj-pelleting of inoculated seeds was found superior to the application of 7.0 t ha-I of lime with inoculated seeds only. A I toxicity and P deficiency were the main problems in these acid soils. For the low-input production of soybeans considerations shOllld be directed to the correction of these factors.